Pemanfaatan Ikan Red Devil (Amphilophus labiatus) sebagai Pupuk Organik Cair dan Produk Pangan Olahan di Sekitar Danau Toba - Grace Happy Hotmauli Simbolon; Leonard Dharmawan; Edi Wiraguna (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2025)
Lake Toba, designated as a National Tourism Strategic Area, faces ecological disruption due to the invasive Red Devil fish (Amphilophus labiatus), which threatens the sustainability of native aquatic species. This study aims to enhance the knowledge of the Tapian Nauli farmer group in Hariara Pohan Village, Samosir Regency, in utilizing the Red Devil fish as Liquid Organic Fertilizer (LOF) and processed food. Methods employed include agricultural extension activities, practical demonstrations, pre-tests and post-tests, and evaluation through questionnaires. Results showed a significant improvement in farmers' knowledge after the extension, with 70% moving from the "poor" to "good" category. The Red Devil fish was successfully processed into LOF through fermentation using molasses, starbio, and pineapple, and into shredded fish (abon) as a food product. Farmers responded positively to the idea of Red Devil abon as a potential household business opportunity, given the fish's abundance and low cost. Evaluation of the extension activities revealed a high level of suitability with an average score of 96.33%, covering material content, delivery methods, and instructional media. This study demonstrates that locally based extension approaches can effectively empower farmers to convert invasive pests into value-added products, while fostering economic opportunities rooted in local resources.